PENGARUH VARIASI ARUS TABUNG TERHADAP KONTRAS PADA PESAWAT SINAR-X HIGH GENERATOR - Asih Puji Utami; Anisa Nur Istiqomah (Poltekkes Kemenkes Semarang, 2020)
Background: The use of exposure factors with high voltage / kV and low tube current / milliAmpere (mA) will provide a low radiation dose to the patient and radiographic results that provide good contrast and can reduce the onset of geometric movements. This research is to find out and study the variation of tube current/ milliAmpere (mA) on the image quality and radiation dose received by patients in the Radiology laboratory of Aisyiyah University, Yogyakarta.Methods: This type of research is an experimental study with a quantitative inferential approach, conducted at the Radiology Laboratory of the University of ‘Aisyiyah Yogyakarta. The independent variable is the tube current variation (32 and 100 mA), the dependent variable is the contras. Data collection was carried out by exposing the radiographic panthom and measuring the radiation dose with the Ray Safe X2 device. Radiograph results were analyzed by contras radiograph. Then the results will be analyzed using descriptive statistical analysis and linear regression. by testing the regression line hypothesis, the statistical test f, the statistical test t, the coefficient of determination.Results: The results showed that there was an influence of changes in tube currents (100 and 32 mA) on Soft tissue-air contrast. While the change in tube current (100 mA and 32mA) does not affect the bone-Soft tissue contrast. In order to reduce the radiation dose received by the patient, it can use a low mA value while still being able to maintain the quality of the image.Conclusions: No influence of mA change (100 and 32) on bone contrast-Soft tissue and there are influence of mA changes (100 and 32) on the contrast of Soft tissue-air.